Resiko Gangguan Pernapasan pada Industri Besi Baja - Joko Susilo; Feny Tunjungsari (CoMPHI Journal: Community Medicine and Public Health of Indonesia Journal, 2022)
Work in steel mills is close to exposure to dust, fumes, and gases. Pollutants from activities in factory workers such as iron dust and other particles can increase the permeability of the respiratory tract mucosa. Iron dust can cause damage to lung surfactant and lung function and quartz can pose a risk of silicosis, lung cancer, cardiovascular disease, and mortality. This study uses several literature reviews through several international journals from 2015 to 2020. Search articles related to the risk of respiratory disorders in steel factories. Exposures to factory workers include metal fumes, dust, silica, acid gases. Respiratory disorders appear in the form of clinical symptoms which are divided into chronic and acute symptoms as well as changes in lungfunction as seen from changes in FVC and FEV1 from spirometry examination. The influencing factors are metallic agents that can be inhaled, the length of time workers are exposed to, working in confined spaces, lack of adequate ventilation, lack of occupational safety and health training, and worker compliance in the use of personal protective equipment. The risk of respiratory disorders in steel industry workers is a decrease in lung function accompanied by acute and chronic respiratory disorders. There are several factors that affect respiratory disorders in workers so that steel production companies are advised to take a comprehensive holistic approach in dealing with the risk of respiratory problems in steel factories.